Analytical model of multiview autostereoscopic 3D display with a barrier or a lenticular plate - Vladimir Saveljev (Journal of Information Display, 2018)
A geometric model of an autostereoscopic 3D display is described herein. This model is based on the geometry of typical display devices and on the projective transformations that provide periodicity in the projective space. The formulas for the transformations between regions and spaces are provided. The model can be applied to the study of an operation of the multiview, integral, plenoptic, and light-field displays. A practical application considered in this paper is the multiview wavelet transform.